Psoriasis Does Not Worsen Outcomes in Patients Admitted for Ischemic Stroke: An Analysis of the National Inpatient Sample. (June 2021) - Edigin, Ehizogie; Kaul, Subuhi; Eseaton, Precious Obehi; Ojemolon, Pius Ehiremen; Patel, Axi; Manadan, Augustine
Psoriasis is a chronic inflammatory state associated with an increased risk of cardiometabolic diseases, stroke, and mortality. Although psoriasis increases the risk of ischemic stroke, whether outcomes, including mortality, are adversely affected is unknown. This study aims to compare inpatient mortality of patients admitted for ischemic stroke with and without psoriasis. The secondary outcome measures were hospital length of stay (LOS), total hospital charges, odds of receiving tissue plasminogen activator (TPA), and mechanical thrombectomy between both groups. Data were obtained from the National Inpatient Sample (NIS) 2016 and 2017 databases using the International Classification of Diseases, Tenth Revision, Clinical Modification codes. Multivariable logistic and linear regression analysis were used accordingly to account for confounders of the outcomes. The combined 2016 and 2017 NIS database comprised over 71 million discharges. Of these, ischemic stroke accounted for 525, 570 hospitalizations and 2425 (0.5%) had a concomitant diagnosis of psoriasis. Patients hospitalized for ischemic stroke with coexisting psoriasis did not have a difference in inpatient mortality (3.5% vs 5.5%; p=0.285) compared with those without psoriasis. However, psoriasis cohort had shorter LOS (5.0 vs 5.7 days; p=0.029) and lower total hospital charges ($60, 471 vs $70, 246; p=0.003) compared with the non-psoriasis cohort. The odds of receiving TPA and undergoing mechanical thrombectomy were not different in both groups. Inpatient mortality, odds of receiving TPA, and undergoing mechanical thrombectomy in patients who had an ischemic stroke with or without psoriasis were not different. However, patients with psoriasis had a significantly shorter LOS and lower hospital charges.